The Influence of Competency and Communication on Employee Performance With Job Satisfaction as an Intervening Variable (Case Study of Employees at KPP Pratama Semarang Gayamsari) - Ririn Sulistyorini; Indarto Indarto; Yuli Budiati (Jurnal Scientia, 2024)
The purpose of this study is to determine how communication and competence affect employee performance while accounting for work satisfaction as a mediating variable. One of the duties of the KPP Pratama Semarang Gayamsari, a division of the Directorate General of Taxes-Ministry of Finance of the Republic of Indonesia, where this study was conducted, is to secure income in the taxes sector. In order to analyze the impact of job contentment on the capabilities of KPP Pratama Semarang Gayamsari employees to mediate competence and communication, researchers used Structural Equation Modeling (SEM) using SmartPLS. A population of 87 KPP Pratama Semarang Gayamsari employees was sampled. Testing shows that the research's conclusions, when all factors are included, show that communication and competence have a positive and substantial impact on job satisfaction, which in turn has a favorable and significant impact on worker performance. Additionally, job satisfaction has the ability to mitigate the significant influence of competence. Provide feedback on KPP Pratama Semarang Gayamsari staff members' performance.